Factors Affecting Teenage Pregnancy at Selected Barangay of Echague Isabela Philippines - Rianne Maie C. Mangaoil; Edmelyn B. Cacayan; Angelito E. Alvarado; Precious Anne R. Ramos; Johanie A. Samut; Trixie Mae E. Rivera; Maricel A. Ricardo; Jinky R. Sanchez (Health Notions, 2021)
Teenage pregnancy affects many teenagers and become a public health concern. The purpose of this research study is to identify the different environmental factors affecting early pregnancy among teenagers in selected Barangay of Echague Isabela. Descriptive-correlational study was conducted among selected teenagers at barangay X, Y and Z of Echague Isabela through non-probability convenience sampling technique. Questionnaire consist of 4 contributing factors; the economic factor, familial factor, peer-pressure factor and educational factor using the Likert scale. Data were gathered through online platforms and face-to-face. The result of the study reveals that there was no significant relationship between the factors that contribute to teenage pregnancy and their profile age, and educational status where C >0.05 on the analysis. There was no significant difference between the factors that contributed to teenage pregnancy when grouped according to their profile age, and educational status where the analysis shows F > 0.05. It indicates that the factors that contribute to teenage pregnancy is not affected by the respondents’ age, and their educational status. It served as resources, to increase awareness and may provide information that could be useful for couples, students, health workers, teachers and parents. Keywords: teenage pregnancy; factors; affects